1979
DOI: 10.1007/bf00347911
|View full text |Cite
|
Sign up to set email alerts
|

Use of δ13C values to determine vegetation selectivity in East African herbivores

Abstract: The quantitative plant species composition of the rumen contents of a large number of individuals from eight East African herbivores was determined by direct visual analysis. All plant species were classified as either C or C, and an estimated δC for the rumen sample was calculated. This estimated value was compared to a measured value determined directly from rumen subsample. The two methods of determining quantitative C and C composition differed by less than 1%, and the isotopic analysis has the advantage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(74 citation statements)
references
References 24 publications
5
69
0
Order By: Relevance
“…Mean 613C values range from near -26%0 for C 3 plants to about -12%o for C 4 species (Smith and Epstein, 1971). This difference in C isotope signature has been used to determine the relative proportions of C 3 and C 4 plants in diets of insect and mammalian herbivores (Boutton et al, 1983;Pinder and Kroh, 1987;Tieszen et al, 1979;Tieszen and Imbamba, 1980), soil organic matter (Dzurec et al, 1985;Tieszen and Boutton, 1989), and aboveground (Ludlow et al, 1976) and root biomasses in species mixtures (Svejcar and Boutton, 1985;Svejcar et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Mean 613C values range from near -26%0 for C 3 plants to about -12%o for C 4 species (Smith and Epstein, 1971). This difference in C isotope signature has been used to determine the relative proportions of C 3 and C 4 plants in diets of insect and mammalian herbivores (Boutton et al, 1983;Pinder and Kroh, 1987;Tieszen et al, 1979;Tieszen and Imbamba, 1980), soil organic matter (Dzurec et al, 1985;Tieszen and Boutton, 1989), and aboveground (Ludlow et al, 1976) and root biomasses in species mixtures (Svejcar and Boutton, 1985;Svejcar et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotopes in feces, which are composed of undigested food matter, gut microbes, digestive secretions, and sloughed epithelial tissues, have been demonstrated in experimental and wild settings to reflect ingested diet in mammalian herbivores and primates (4,(40)(41)(42)(43). Digestive processes along the mammalian gastrointestinal tract do not seem to consistently alter the stable isotopic composition of feces relative to diet (44, 45).…”
mentioning
confidence: 99%
“…Despite the fact that species-specific metabolism would be expected to affect the isotope ratios found in faeces and faecal samples represent only the non-digested plant materials, controlled feeding trials and field based studies have shown an agreement between faecal and dietary  13 C and  15 N in African herbivores (Codron and Codron, 2009;Codron et al, 2005c;Tieszen et al, 1979). We therefore suggest that our relative differences reflect dietary differences between the herbivore species, either in terms of the taxonomic, geographic, or topographic sources of their food, or in physiological differences between the consumed plants.…”
Section: Study Caveats and Future Researchmentioning
confidence: 99%